Outbreak of Edwardsiella tarda in Cultured Pangasius hypophthalmus (Sauvage, 1878) - Joseph, Toms C.; Dinesh, R.; Shaheer, P.; Murugadas, V.; Rekha, M.; Lalitha, K. V. (Fishery Technology, 2019)
Mass mortality and morbidity were reported from cultured Pangasius hypophthalmus (Sauvage, 1878) in an aquaculture farm in Kerala, India. Pure bacterial cultures were isolated and identified as Edwardsiella tarda from body ulcers and internal organs of moribund P. hypophthalmus and from sediments of farms without an outbreak. LD50 in P. hypophthalmus models of the isolates from diseased fish (1.25 X 105 CFU per fish) and isolates from sediment samples (1.18 X 105 to 3.8 X 105 CFU per fish) were similar. PCR targeting esaV gene was unable to discriminate the pathogenic and non-pathogenic E. tarda. However, ERIC-PCR followed by dendrogram analysis differentiated isolates based on the presence of esaV gene. The isolates that did not carry the esaV gene also were found to be virulent in P. hypophthalmus fingerlings. Hence it can be assumed that the type III secretory system along with other virulence determinants contributes to virulence by E. tarda in fishes.